Rift Valley fever epidemiology: shifting the paradigm and rethinking research priorities - Rostal, M.K.; Thompson, P.N.; Anyamba, A.; Bett, Bernard K.; Cêtre-Sossah, C.; Chevalier, V.; Guarido, M.; Karesh, W.B.; Kemp, A.; LaBeaud, A.D.; Lubisi, A.; Matthews, L.; et al. (Elsevier, 2025)
Rift Valley fever (RVF), a zoonotic mosquito-borne viral disease with erratic occurrence and complex epidemiology, results in substantial costs to veterinary and public health and national economies. Since 1985, RVF virus (RVFV) epidemiology has focused on epidemics triggered by flood-induced emergence of transovarially infected mosquitoes, following an interepidemic period during which RVFV persists primarily in floodwater Aedes spp. mosquito eggs, with potential for low-level interepidemic circulation. In this Personal View, we challenge this classic framework of RVFV epidemiology, presenting instead a spectrum of RVFV dynamics ranging from epidemic to hyperendemic. We present the case for RVFV being maintained in a variable reservoir system of livestock, wildlife, and mosquitoes, with or without transovarial transmission. We highlight that sufficient evidence supports a shift in the paradigm of RVF epidemiology to embrace a more nuanced understanding of the spectrum of RVFV dynamics and call for more research into understanding the drivers of RVFV dynamics in hyperendemic areas.